2016
DOI: 10.1038/hdy.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

The fate of W chromosomes in hybrids between wild silkmoths, Samia cynthia ssp.: no role in sex determination and reproduction

Abstract: Moths and butterflies (Lepidoptera) have sex chromosome systems with female heterogamety (WZ/ZZ or derived variants). The maternally inherited W chromosome is known to determine female sex in the silkworm, Bombyx mori. However, little is known about the role of W chromosome in other lepidopteran species. Here we describe two forms of the W chromosome, W and neo-W, that are transmitted to both sexes in offspring of hybrids from reciprocal crosses between subspecies of wild silkmoths, Samia cynthia. We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The above designs assume a 'dominant W' sex determination system in DBMie the existence of a Fem orthologueor functionally similar upstream signal. However, evidence suggests that the ancestral 'Z counting' mechanismwhere sex is determined by dosage of Z-linked genes -may be present even in lepidopterans with a WZ/ZZ sex chromosome arrangement (Yoshido et al, 2016). Although the ultimate sex-determination signals in DBM have yet to be identified, use of Masc is not dependent on the dominant W system.…”
Section: Discussionmentioning
confidence: 99%
“…The above designs assume a 'dominant W' sex determination system in DBMie the existence of a Fem orthologueor functionally similar upstream signal. However, evidence suggests that the ancestral 'Z counting' mechanismwhere sex is determined by dosage of Z-linked genes -may be present even in lepidopterans with a WZ/ZZ sex chromosome arrangement (Yoshido et al, 2016). Although the ultimate sex-determination signals in DBM have yet to be identified, use of Masc is not dependent on the dominant W system.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous loss of a nonfunctional W chromosome may be easier than expected: in a wild silkmoth Samia cynthia , the W chromosome does not have a sex‐determining function, and Z0 females are frequently obtained in experimental crosses between subspecies (Yoshido et al. ). Wolbachia has previously been found to be associated with the loss and birth of W chromosomes in the woodlouse Armadillidium vulgare (Rigaud et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Ostrinia moths, a female-determining function is thought to have been lost from the W chromosome in Wolbachia-infected matrilines (Sugimoto and Ishikawa 2012). Spontaneous loss of a nonfunctional W chromosome may be easier than expected: in a wild silkmoth Samia cynthia, the W chromosome does not have a sex-determining function, and Z0 females are frequently obtained in experimental crosses between subspecies (Yoshido et al 2016).…”
Section: Wolbachia Evolve?mentioning
confidence: 99%
“…It was also suggested that wFem lines have lost the W chromosome, and rely on wFem for female development as curing the infection with antibiotics results in all-male offspring (Kern et al, 2015). Later work demonstrated that Wolbachia itself was responsible for the disruption of maternal Z chromosome inheritance in wFem infected females, as well as the feminisation of female ZO individuals that have lost the female-determining W chromosome (Kageyama et al, 2017).…”
Section: Feminisationmentioning
confidence: 99%